Literature and public administration ethics - Marini Frank
Interest in professional ethics education for public administrators has booming for the past two decades, and teaching public administration ethics entails a variety of approaches. This article argues that literature is an effective main source for exploring public administration ethics. Several reasons support this argument: students are receptive to literature and learn from it: there is an element of storytelling in our everyday approach as well as in our scholarly approach to ethics; literature offers an empathetic prosaic methods with shor-lived value contributes to lifelong education as well as professional training. This article offers examples of how we can use certain works of literature to teach publi
Keywords: Public Administration -- Study and Teaching; Public Administration